EFEKTIVITAS PROGRAM PERCEPATAN PENURUNAN STUNTING DI KECAMATAN AMARASI SELATAN, KABUPATEN KUPANG (Studi Kasus Pada Desa Nekmese Dan Desa Retraen) - Maria Wilhelmina Wila Uli; Laurensius P. Sayrani; Made N. Andayana (Journal Education and Government Wiyata, 2025)
Effectiveness and efficiency are often linked. If you achieve a goal or suggestion as planned, you can say it is effective, but this doesn't automatically mean it is efficient. Even if something is more effective, it doesn't automatically mean it's efficient. If a goal has been achieved as planned, it can be said to be effective. But if a job isn't finished on time, it can be said to be ineffective. Effectiveness is how well we achieve our goals and how well we balance different values. It is important to reduce stunting as early as possible to avoid having a negative impact on children's growth and development in the long term. Stunting affects brain development, so children don't achieve their full potential in terms of intelligence. This can mean they are less productive as adults. Stunting also makes children more vulnerable to disease. Stunted children are more likely to have chronic diseases as adults. We can see how well the programme to reduce stunting in Nekmese Village (where lots of children are stunted) and Retraen Village (where fewer children are stunted) in South Amarasi District, Kupang Regency, is working. Every year, there are fewer cases, but there is still a problem.